Key technologies for the development of intelligent things - Ling-ling SUN; Jiang-tao SU; Xi-wei HUANG; Jie JIN; Wen-jun LI; Xiao-jun WANG (物联网学报)
Intelligent things are intelligent terminals and systems based on software-hardware integrated platforms which are capable of smart sensing, smart processing, smart connection, and smart human-computer interaction. The key technologies for the development of intelligent things, including integrated circuit technology, sensor technology, software-hardware integrated platform, and security technology were discussed, together with opportunities and challenges, to promote the research and development of intelligent things.